Would God Forgive? Public Attitudes Toward Sex Offenders in Places of Worship. (August 2020) - Dum, Christopher P.; Socia, Kelly M.; Long, Brooke L.; Yarrison, Fritz
Previous research has explored the impact of faith and religion on recidivism. However, it focused primarily on violent offenders, drug users, tax evaders, and so on. Missing is an examination of registered sex offenders (RSOs) and the role religion and religiosity play in facilitating reentry. Religiosity and religious organizations may play a role in increasing social bonds and reducing isolation in RSOs. In addition, being surrounded by a faith-based community could act as a catalyst for identity transformation from a RSO to a community member. Using a national online sample of U.S. adults, this research investigates individual's support of policies controlling sex offenders in religious communities and how demographic characteristics affect these views. Results suggest that Protestants and Other (non-Catholic) Christians are the most accepting of RSOs in places of worship. In addition, the stronger an individual's faith, the less accepting they are of RSOs. Older, liberal, and educated respondents are more accepting of RSOs.